Addressing Limitations and Future Directions in Assessing Risk Factors for Pulmonary Complications after Femur Fracture Surgery in Elderly Patients [Letter] - Liu Z; Tian M; Duan L (Clinical Interventions in Aging)
Zhongxing Liu,1,2,* Mengzhe Tian,3,* Lincheng Duan2 1Dujiangyan Traditional Chinese Medicine Hospital, Chengdu, Sichuan, People’s Republic of China; 2Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China; 3Chengdu Sport University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lincheng Duan, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China, Email lincheng@stu.cdutcm.edu.cn